PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Nugroho, Susilo Dwi; Jayanti, Fitri Dwi (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
This study examines the effect of good corporate governance represented by gender and age diversity of the board of directors, the size of the board of commissioners, and the frequency of board of directors meetings on the company's financial performance calculated by ROE (Return on Assets). The sample of this study was 62 manufacturing companies listed on the IDX in 2020-2022 which were obtained through purposive sampling techniques. This study uses multiple regression analysis methods. The results of the study indicate that gender diversity of the board of directors has a positive and significant effect on financial performance, age diversity of the board of directors has a positive and significant effect on financial performance, the size of the board of commissioners has a positive and significant effect on financial performance, the frequency of board of directors meetings has a positive and significant effect on financial performance.